The carboxyl terminal trimer of procollagen I induces pro-metastatic changes and vascularization in breast cancer cells xenografts - Visigalli, Davide (BioMed Central, 2009)
BACKGROUND: The COOH terminal peptide of Pro-collagen type I (PICP, also called C3) is chemotactic for endothelial melanoma and breast cancer cells. PICP induces the expression of Metalloproteinases-2 and -9, of Vascular endothelial growth factor and of the chemokine CXCL-12 receptor CXCR4 in MDA MB231 breast carcinoma cells in vitro. METHODS: We used a model of xenografts in BalbC/nude mice obtaining tumors by implanting in contro-lateral subcutaneous positions MDA MB231 cells added or not with purified PICP and studied the earlier phases of tumor development, up to 48 days from implant, by histology, immunostain and in situ hybridization. RESULTS: Addition of PICP promotes rapid vascularization of the tumors while does not affect mitotic and apoptotic indexes and overall tumor growth. PICP-treated, relative to control tumors, show up-modulation of Vascular endothelial factor, Metalloproteinase-9 and CXCR4, all tumor prognostic genes; they also show down-modulation of the endogenous Metalloproteinase inhibitor, reversion-inducing-cysteine-rich protein with kazal motifs, and a different pattern of modulation of Tissue Inhibitor of Metalloproteinase-2. These changes occur in absence of detectable expression of CXCL-12, up to 38 days, in control and treated tumors. CONCLUSION: PICP has an early promoting effect in the acquisition by the tumors of prometastatic phenotype. PICP may be play a relevant role in the productive interactions between stroma and tumor cells by predisposing the tumor cells to respond to the proliferation stimuli ensuing the activation of signaling by engagement of CXCR4 by cytokines and by fostering their extravasion, due to the induction of increased vascular development.